Knapsack sprayer doubles as fertilizer applicator - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
In West Africa scientists have shown that nitrogen applied in solution is the best fertilizer for rice grown in mangrove swamps. Granular fertilisers tend to get washed away by the twice dally flooding. Scientists at the West African Rice...